Digital Survivance Mediatization and the Sacred in the Tribal Digital Activism of the #NoDAPL Movement. - Clark, L.
To explore the role of contestation in mediatization processes, this article utilizes digital and visual methods to analyze instances of Indigenous digital survivance. Focusing on recent examples at the heart of the #NoDAPL movement allows us to flesh out and argue for a decolonizing approach to the study of mediatization, which we define, following Clark (2011), as the process by which collective uses of communication media (1) extend the development of independent media industries and their circulation of narratives, (2) contribute to new forms of action and interaction in the social world, and (3) give shape to how we think of humanity and our place in the world. The article therefore concludes with suggestions regarding the further development of methodological approaches to studying processes of mediatization in relation to contestations over normative claims and pragmatic concerns regarding the role of media systems in our collective future.